Math

How is 1/(x-2) = (2x - 6)/(x + 6) + 1 rewritten as 1/(x - 2) = 3x/(x + 6)? I don't understand.

  1. 👍 0
  2. 👎 0
  3. 👁 121
  1. right side
    = (2x-6)/(x+6) + 1
    = (2x-6)/(x+6) + (x+6)/(x+6)
    now we have a common denominator
    = (2x-6 + x+6)/(x-6
    = 3x/(x+6)
    as you required.

    1. 👍 0
    2. 👎 0
    posted by Reiny

Respond to this Question

First Name

Your Response

Similar Questions

  1. Alg

    Does log eqaul to baswe 10? So would logb=a be rewritten as 10^a=b? AND Why would ln5=x be rewritten as e^x=5? is it because ln also means ln(e) the e is supposed to be lowered idk how.

    asked by Amy~ on June 2, 2010
  2. Math2(Please help)

    Directions:Solve and explain the inequality using words.Tell which wa shading goes. Problem: x+3=>2x+1 and -4x

    asked by margie on April 10, 2007
  3. Math

    1. Find the exact value of 2tan pi/12 / 1-tan^2 pi/12 root 3/3? 2. Given tanθ = -1/3 and with θ in quadrant IV, find the exact value of cos2(θ) 4/5 3. Exact value of cos^2 67.5 - sin^2 67.5 root3 /2 4. The expression cos 3θ

    asked by mysterychicken on June 3, 2013
  4. Spanish

    Please check-I have to rewrite with an indirect object pronoun 1. Escribo una carta a mi abuela. Rewritten as :Le escribo una carta a mi abuela. 2.Mando una tarjeta postal a mis amigos. Rewritten as:Les mando una tarjeta postal a

    asked by Ben. on November 7, 2011
  5. Math

    How is 1/(x-2) = (2x - 6)/(x + 6) + 1 rewritten as 1/(x - 2) = 3x/(x + 6)? I don't understand.

    asked by Anonymous on May 8, 2014
  6. Algebra

    Could someone tell me what I am doing right or wrong? Problem Two: 5/9 + (2/9)x = 25/7 + (6/7)x – 2/3 Like signs are not collected at the beginning. This would make the equation unequal. To make both sides equal we first

    asked by Aria on April 29, 2011
  7. maths

    how do i factorise this?: p^2+2p+1-t^2 thx. p^2 + 2p + 1 - t^2 = (p+1)^2 - t^2 This is the difference of two squares, so it can be rewritten =(p+1+t)(p+1-t)

    asked by Emma on July 11, 2007
  8. Math

    10e^(3x-7)= 5 So what I've done is rewritten it as: (3x-7)ln10e = ln5 Now I'm a little lost as to what to do next...

    asked by D.S. on April 9, 2012
  9. Math-Calculus

    Posted question rewritten lim x-> -1 108(x^2+2x)(x+1)^3 ____________________ (x^3+1)^3 (x-1)

    asked by Anonymous on February 7, 2010
  10. geometry/math

    What are the components of a good definition? Can all definitions be rewritten as biconditionals?

    asked by hiii on June 27, 2016

More Similar Questions